Morpho-physiology and metabolite content of Cosmos caudatus Kunth. and yellow and orange Cosmos sulphureus Cav. - ISMAIL SALEH; SANDRA ARIFIN AZIZ; MAYA MELATI; NURI ANDARWULAN (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Saleh I, Aziz SA, Melati M, Andarwulan N. 2023. Morpho-physiology and metabolite content of yellow and orange Cosmos sulphureus Cav. and Cosmos caudatus Kunth. Biodiversitas 24: 5739-5746. Cosmos sp., known as kenikir in Indonesia, is an underutilized vegetable commodity. Cosmos sulphureus Cav.  (C. sulphureus), with orange and yellow flowers, is commonly found as an ornamental plant. C. sulphureus can also be used as vegetable crops, although the Cosmos species widely used as a vegetable is Cosmos caudatus Kunth. (C. caudatus). This study investigated the growth, shoot production, primary and secondary metabolite content, and antioxidant activity of yellow and orange C. sulphureus and C. caudatus. This experiment was arranged using a Randomized Completely Block Design (RCBD) with one factor: Cosmos species (yellow and orange C. sulphureus and C. caudatus) with six replications. The result showed that plant height, leaf number, and branch number were not significantly different among the three Cosmos studied; however, the shoot weight per plant of orange C. sulphureus was significantly higher than the others. The antioxidant activity and phenol content of C. sulphureus were lower than that of C. caudatus. Meanwhile, crude fiber, flavonoid, anthocyanin, and carotenoid content were not significantly different among the three kinds of Cosmos. Orange C. sulphureus could be a functional vegetable, although its antioxidant activity is lower than C. caudatus.